2018
DOI: 10.1523/jneurosci.3022-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Decoding of Bistable Sounds Reveals an Effect of Intention on Perceptual Organization

Abstract: Auditory signals arrive at the ear as a mixture that the brain must decompose into distinct sources based to a large extent on acoustic properties of the sounds. An important question concerns whether listeners have voluntary control over how many sources they perceive. This has been studied using pure high (H) and low (L) tones presented in the repeating pattern HLH-HLH-, which can form a bistable percept heard either as an integrated whole (HLH-) or as segregated into high (H-H-) and low (-L-) sequences. Alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…A relatively weak classification performance for bistable auditory streaming of triplets was recently reported for MEG recordings (Billig et al, 2018; Sanders et al, 2018). Those studies also found accuracies <60%, despite comparing three different classifiers and using a larger pool of subjects and more experimental blocks.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A relatively weak classification performance for bistable auditory streaming of triplets was recently reported for MEG recordings (Billig et al, 2018; Sanders et al, 2018). Those studies also found accuracies <60%, despite comparing three different classifiers and using a larger pool of subjects and more experimental blocks.…”
Section: Discussionmentioning
confidence: 88%
“…Noninvasive recordings in humans found neural correlates of persistent perceptual states in streaming of triplets in AC and the intraparietal sulcus (Cusack, 2005; Gutschalk et al, 2005; Snyder et al, 2006; Hill et al, 2011; Billig et al, 2018). Percept-related MEG responses were localized to AC, occurring ∼60 ms after the onset of tone B and had larger amplitudes at the 2-stream percept (Gutschalk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDTBOX uses a moving-window approach in which the trial data (usually containing a baseline period and epoched and truncated, depending on the individual research question) is analysed within an analysis time window , which is moved through the entire trial in small (overlapping or non-overlapping) steps, each time containing the next step’s data. It is also possible to use a pre-defined time-period of interest instead (e.g., Billing et al, 2018), but we will focus on the moving-window approach in this paper. Each analysis step/window is treated as an independent analysis.…”
Section: Support Vector Regression (Svr) Analysis In Ddtboxmentioning
confidence: 99%
“…Listeners can perceive sound series as multiple streams when their duration and frequencies are in a certain range. The number of streams can be switched according to the interplay of attention and acoustic features [19][20][21]. These studies on the interaction between top-down and bottom-up processes motivated us to ask whether meter perception might also switch depending on the attribute of sound events that we focus on.…”
Section: Introductionmentioning
confidence: 99%